2022
DOI: 10.1038/s12276-022-00806-z
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA ROCK1, a novel circRNA, suppresses osteosarcoma proliferation and migration via altering the miR-532-5p/PTEN axis

Abstract: As the most prevalent bone tumor in children and adolescents, the pathogenesis and metastasis of osteosarcoma (OS) remain largely unclear. Here, we investigated the expression and function of a novel circular RNA (circRNA), circROCK1-E3/E4, which is back-spliced from exons 3 and 4 of Rho-associated coiled-coil containing protein kinase 1 (ROCK1) in OS. We found that circROCK1-E3/E4, regulated by the well-known RNA-binding protein quaking (QKI), was downregulated in OS and correlated with unfavorable clinical f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…For example, the circular RNA ciRs7 can adsorb miR-7 to relieve the repression of its target genes [ 12 , 13 ]. circROCK1-E3/E4 suppresses tumor growth and metastasis by upregulating PTEN through miR-532-5p sponging [ 14 ]. Analogously, circ_001678 can sponge miR-326 to increase ZEB1 expression and promote immune escape in NSCLC [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the circular RNA ciRs7 can adsorb miR-7 to relieve the repression of its target genes [ 12 , 13 ]. circROCK1-E3/E4 suppresses tumor growth and metastasis by upregulating PTEN through miR-532-5p sponging [ 14 ]. Analogously, circ_001678 can sponge miR-326 to increase ZEB1 expression and promote immune escape in NSCLC [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The secondary structure of pre-mRNAs brings forming exons of circRNA into close proximity and consequently promotes circRNA biogenesis. A previous study indicated that QKI targets the introns flanking the circRNA-forming exons of ROCK1 and NOTCH1 to promote cyclization [ 38 , 39 ]. Consistent with these studies, we found that circCABIN1 has binding sites located in introns 24 and 29 of CABIN1 pre-mRNA that circCABIN1 biogenesis is enhanced via binding to recognition elements within introns in the vicinity of splice sites associated with circCABIN1 formation.…”
Section: Discussionmentioning
confidence: 99%
“…The study of Liu et al 31 showed that circROCK1-E3/E4, produced from exons 3 and 4 of ROCK1 precursor mRNA, was downregulated in patients with osteosarcoma and associated with poor prognosis. Downregulation of circROCK1-E3/E4 promoted proliferation and migration in U2OS and HOS cells.…”
Section: The Role and Regulatory Mechanism Of Circular Rna In The Occ...mentioning
confidence: 99%